Content Analysis of Podcast via OTT Radio Service in Thailand - Prawornrat Raweng (Journal of Digital Communications, 2020)
This article is to present the results of podcast content analysis in order to describe 1) Over the top services of podcast 2) radio program types of podcast and 3) radio program formats of podcast. The content analysis was conducted using a sampling of podcast programs in Thai language collected from December 2017 to February 2018, totaling 104 episodes from podcast application for iPhone. The result of content analysis shows that, from the service provider category, podcast from user generated content was found as the top services of podcast, followed by podcast from mass media providers. From the income category, non-profitable podcast was the most found out in the sampling, followed by advertising-based on podcast. From the content category, mass content and niche content were found in the same amount in the market. For radio program types of podcast, economic development, society, quality of life and environment are the most popular program types, followed by entertainment, education promotion, ethics, arts, cultures, health science, sports, news, and lastly, democratic education respectively. For radio program formats of podcast, conversational program was the most found out from the sampling, followed by interview program, straight talk program, descriptive program, discussion program, news program and variety program, respectively.